Scratch-resistant and impact-resistant photoelectric glass cover plate as well as preparation method and application thereof

By precisely controlling the glass composition and process parameters, the content of SiO2, Al2O3, CaO and other components is optimized, and the shortcomings of existing glass covers in terms of scratch resistance, impact resistance, spectral transmittance and chemical stability are solved, and a high-performance photoelectric glass cover is achieved.

CN119912159APending Publication Date: 2025-05-02CNBM PHOTONICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411362811.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing glass cover plates have shortcomings in terms of scratch resistance, impact resistance, spectral transmittance, haze and chemical stability, which are difficult to meet the needs of modern touch technology for high-performance protection solutions.

Method used

By precisely controlling the content of SiO2, Al2O3, CaO, MgO, K2O, Na2O, Li2O, ZrO2, B2O3, Bi2O3 and CeO2, the composition and process parameters of the glass are optimized, the viscosity and crystallization tendency of the glass are reduced, and the thermal stability and chemical stability of the glass are improved.

Benefits of technology

It achieves scratch resistance, impact resistance, excellent spectral transmittance, low haze and good chemical stability, improves the comprehensive performance of glass, and is suitable for the application of touch screen components of digital products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912159A_ABST
    Figure CN119912159A_ABST
Patent Text Reader

Abstract

The invention relates to a special glass material, in particular to a scratch-resistant and impact-resistant photoelectric glass cover plate as well as a preparation method and application thereof. The high-temperature-resistant ceramic material is prepared from the following components in parts by weight: 55.0 to 63.0 parts of SiO2, 9.0 to 15.0 parts of Al2O3, 0.1 to 2.0 parts of CaO, 4.0 to 8.0 parts of MgO, 3.0 to 7.0 parts of K2O, 9.0 to 15.0 parts of Na2O, 0.5 to 2.0 parts of Li2O, 0.5 to 3.0 parts of ZrO2, 2.0 to 6.0 parts of B2O3, 30 to 3.0 parts of Bi2O3 and 0.1 to 1.0 part of CeO2. The cover plate glass provided by the invention not only has good performance in the aspects of scratch resistance and impact resistance, but also has excellent spectral transmittance, relatively low haze and good chemical stability, meanwhile, the cover plate glass can be endowed with the performance of eliminating stray light so as to avoid light leakage of a screen, and the processability is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a special glass material, and in particular to a scratch-resistant and impact-resistant photovoltaic glass cover plate and a preparation method and application thereof. Background Art

[0002] The cover plate is located at the outermost layer of the touch screen, and its main function is to protect the touch screen. Since it is in direct contact with the outside world, in addition to the surface finish, thickness and other parameter requirements, the properties that determine the quality of the cover plate also include high hardness, pressure resistance, scratch resistance, etc. Compared with cover plates made of other materials, glass cover plates (Cover Glass or Cover Lens) have obvious advantages in these important parameters, so they have gradually become the mainstream protection solution for various touch technologies.

[0003] Glass is a brittle material, easy to break, and the cover glass is very thin (such as 1.3mm). In order to make the glass protect the display screen and not easy to break, it must be chemically tempered. Chemically tempered glass is manufactured using a low-temperature ion exchange process. The so-called low temperature system refers to the exchange temperature not higher than the glass transition temperature, which is relative to the high-temperature ion exchange process above the transition temperature and below the softening point. The simple principle of the low-temperature ion exchange process: in an alkali salt solution at a certain temperature, the ions with smaller radius in the surface layer of the glass are exchanged with the ions with larger radius in the solution, such as lithium ions in the glass are exchanged with potassium or sodium ions in the solution, and sodium ions in the glass are exchanged with potassium ions in the solution. The difference in the volume of alkali ions is used to form an embedded extrusion stress on the surface layer of the glass, thereby achieving the effect of enhancing the strength of the glass. However, the manufacturing process of this material is complicated, the viscosity of the glass itself is relatively high, and the bubbles in the glass liquid are not easy to eliminate during the melting process. In addition, the subsequent strengthening treatment process after the glass is formed also needs to be strictly formulated. Summary of the invention

[0004] In order to address the deficiencies in the prior art, the purpose of the present invention is to provide a scratch-resistant and impact-resistant photoelectric glass cover plate and a preparation method and application thereof. The cover glass provided by the present invention has good performance. Not only in terms of scratch resistance and impact resistance, the cover glass also has excellent spectral transmittance and low haze. At the same time, the glass can produce a black stray light eliminating layer under a reducing atmosphere, which can give the cover glass the performance of stray light eliminating, thereby avoiding light leakage from the screen and further optimizing the display effect of the screen. It also has good chemical stability and processing performance.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] In a first aspect, a scratch-resistant and impact-resistant photovoltaic glass cover is composed of the following components in parts by weight:

[0007] SiO2 55.0~63.0 parts, Al2O3 9.0~15.0 parts, CaO 0.1~2.0 parts, MgO 4.0~8.0 parts, K2O3.0~7.0 parts, Na2O 9.0~15.0 parts, Li2O 0.5~2.0 parts, ZrO2 0.5~3.0 parts, B2O3 2.0~6.0 parts, Bi2O3 0~3.0 parts, CeO2 0.1~1.0 parts; the sum of the weight parts of each component is 100 parts.

[0008] The present invention is based on the above-mentioned glass system. By controlling the contents of CaO, K2O, Na2O and B2O3, the viscosity of molten glass can be reduced and the difficulty of glass molding can be reduced; by controlling the contents of SiO2, Al2O3, Li2O, Na2O and K2O, the tendency of glass crystallization can be reduced; by controlling the contents of K2O, Na2O, CaO, B2O3, Bi2O3 and CeO2, the difficulty of glass clarification can be reduced, and defects such as bubbles in the glass melting process can be reduced. The mechanical properties of glass materials such as scratch resistance and drop resistance are improved by combining Li2O, CaO, MgO, ZrO2 with SiO2 and Al2O3. By adjusting the contents of Al2O3, Li2O, MgO and CaO, the tendency of glass crystallization is effectively reduced, and the permeability of the glass after molding is further improved. The ion exchange capacity of the glass material is improved under the joint action of Na2O, K2O and ZrO2.

[0009] In addition, the integrated effect of SiO2, CaO, B2O3 and MgO in the present invention jointly improves the thermal stability and chemical stability of the glass. SiO2, as the main component, provides the basis of the structure; the synergistic effect of CaO, B2O3 and CaO adjusts the thermal expansion coefficient and enhances the chemical stability. The addition of MgO further improves the corrosion resistance of the glass in complex environments and prolongs its service life.

[0010] In the glass system provided by the present invention, the integrated effect of SiO2, CaO, B2O3 and MgO jointly improves the thermal stability and chemical stability of the glass. SiO2, as the main component, provides the basis of the structure; the synergistic effect of CaO, B2O3 and CaO adjusts the thermal expansion coefficient and enhances the chemical stability. The addition of MgO further improves the corrosion resistance of the glass in complex environments and prolongs its service life.

[0011] In summary, the scratch-resistant and impact-resistant photoelectric glass cover provided by the present invention contains SiO2, Al2O3, CaO, MgO, K2O, Na2O, Li2O, ZrO2, B2O3, Bi2O3, and CeO2 at the same time. By precisely controlling the components and contents of SiO2, Al2O3, CaO, MgO, K2O, Na2O, Li2O, ZrO2, B2O3, Bi2O3, and CeO2, excellent comprehensive performance, including scratch resistance, impact resistance, haze, stray light elimination, and optical transmittance, is achieved.

[0012] In a second aspect, a method for preparing the scratch-resistant and impact-resistant photovoltaic glass cover plate comprises the following steps:

[0013] Mixing the raw materials of the glass material according to the proportion of each component, and mixing them evenly to obtain a mixture;

[0014] The mixture is melted at 1480-1580°C, stirred, clarified, and molded at 1350-1400°C.

[0015] In a third aspect, a use of the above-mentioned scratch-resistant and impact-resistant optoelectronic glass cover in the preparation of a touch screen component for a digital product.

[0016] The beneficial effects of the present invention are:

[0017] 1. The scratch-resistant and impact-resistant photovoltaic glass cover provided by the present invention has high optical and mechanical properties through the selection and content adjustment of glass system components. Experiments show that its bending strength can reach 172MPa, the maximum optical transmittance of a 2mm glass sample can reach 92.1%, and the minimum transmittance of a 1mm glass sample after reduction is 1.1%.

[0018] 2. The scratch-resistant and impact-resistant photoelectric glass cover provided by the present invention has a surface compressive stress (CS) of up to 708MPa and a stress layer depth (DOL) of up to 49μm after only one chemical strengthening. At the same time, its acid resistance and moisture resistance are level 1, and its mechanical properties and processing properties are good, and it has excellent scratch resistance and impact resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0020] Figure 1 It is a comparative curve diagram of the transmittance of the 2 mm thick glass material in the wavelength range of 350 nm to 1000 nm of Example 2 of the present invention and Comparative Example 1.

[0021] Figure 2It is a comparison chart of CS and DOL of glass materials of Examples 1 to 9 and Comparative Examples 1 to 6. DETAILED DESCRIPTION

[0022] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0023] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0024] A typical embodiment of the present invention provides a scratch-resistant and impact-resistant photovoltaic glass cover, which is composed of the following components in parts by weight:

[0025] SiO2 55.0~63.0 parts, Al2O3 9.0~15.0 parts, CaO 0.1~2.0 parts, MgO 4.0~8.0 parts, K2O3.0~7.0 parts, Na2O 9.0~15.0 parts, Li2O 0.5~2.0 parts, ZrO2 0.5~3.0 parts, B2O3 2.0~6.0 parts, Bi2O3 0~3.0 parts, CeO2 0.1~1.0 parts; the sum of the weight parts of each component is 100 parts.

[0026] In the present invention, SiO2 is a glass-forming oxide. As the main constituent of glass, it provides the basic framework of the structure and gives the glass good chemical stability and mechanical strength. The appropriate SiO2 content can reduce the thermal expansion coefficient of the glass and improve the thermal stability, chemical stability, softening temperature, heat resistance, hardness and mechanical strength of the glass. Too high a SiO2 content may lead to an increase in the melting point and difficulty in processing; too low a SiO2 content may weaken the chemical stability and mechanical strength of the glass. SiO2 is preferably 55.0 to 60.0 parts, 56.5 to 59.0 parts, 57.0 to 58.5 parts, 57.5 to 58.5 parts, 57.6 to 58.2 parts, 57.8 to 58.2 parts, etc.

[0027] Al2O3 is an essential component for improving the chemical stability of glass, which can reduce the tendency of glass crystallization. It is also a component for improving the hardness and mechanical strength of glass and increasing the tensile elastic modulus. In the glass network structure, alumina is a network intermediate oxide, between the network generator and the network exogenous body. Al2O3 is preferably 9.0 to 14.5 parts, 9.5 to 15.0 parts, 9.5 to 14.5 parts, 10.0 to 13.0 parts, 10.2 to 13.0 parts, 11.0 to 13.0 parts, 11.5 to 12.5 parts, etc.

[0028] In the present invention, the introduction of CaO can increase the chemical stability and mechanical strength of the glass, but when the amount introduced is large, the glass is prone to crystallization and the thermal stability of the glass is reduced. At the same time, CaO can reduce the viscosity of the glass at high temperatures, which is conducive to clarification; the introduction of MgO can improve the thermal stability of the glass, and the introduction of MgO will reduce the thermal expansion coefficient of the glass, but too much MgO will increase the viscosity of the glass, resulting in difficulty in glass molding. MgO and CaO jointly enhance the mechanical strength and chemical durability of the glass in the present invention. The addition of MgO is particularly helpful to reduce the increase in the thermal expansion coefficient caused by CaO. CaO is preferably 0.1 to 1.5 parts, 0.1 to 1.0 parts, 0.1 to 0.9 parts, 0.3 to 0.7 parts, etc. MgO is preferably 5.0 to 8.0 parts, 5.5 to 8.0 parts, 5.5 to 7.0 parts, 5.5 to 6.5 parts, etc.

[0029] In the present invention, K2O and Na2O are the network oxides of the glass. Alkali metal ions are easy to move and diffuse in the glass, which can reduce the viscosity of the glass during high-temperature melting and make the glass easy to melt. They are good fluxing agents, but the amount of introduction should not be too much. Excessive introduction will increase the thermal expansion coefficient of the glass and reduce the chemical stability, thermal stability and mechanical strength of the glass. In addition, Na2O in the glass + Chemical strengthening is also called ion exchange strengthening. Its principle is to place the glass in molten potassium nitrate at a certain temperature to make the small radius ions (such as Na + ) and large radius ions in molten salts (such as K + ) is replaced, thereby generating a "squeezing" effect on the glass surface, forming a surface compressive stress layer, and improving the mechanical strength of the glass material. K2O is preferably 3.0-6.0 parts, 4.0-7.0 parts, 4.0-6.0 parts, 4.0-5.5 parts, 4.5-6.0, 4.5-5.5, 4.5-5.0, 4.5-4.9 parts, etc. Na2O is preferably 9.0-13.0 parts, 10.0-13.0 parts, etc.

[0030] In the present invention, Li2O can combine with oxygen atoms in the glass network to form Li-O bonds, which helps to strengthen the network structure of the glass and improve the physical properties of the glass. Moreover, the introduction of Li2O in the present invention can reduce the tendency of crystal formation during the cooling and solidification of the glass, help maintain the amorphous state of the glass, and improve the optical transparency of the glass, thereby making the glass more transparent, improving the optical transmittance of the glass, and reducing the haze of the glass. However, it should be noted that the amount of Li2O used needs to be precisely controlled. Excessive Li2O will reduce the chemical stability of the glass and may cause the glass to be more susceptible to crystallization and phase separation. Li2O is preferably 0.8 to 2.0 parts, 0.8 to 1.5 parts, 0.8 to 1.2 parts, etc.

[0031] In the present invention, ZrO2 is a glass intermediate oxide, which has the effect of improving chemical stability and preventing the exposure of alkali metal and alkaline earth metal ions, and is also an important component for improving the tensile elastic modulus, which is very helpful for improving the hardness of glass after chemical strengthening. ZrO2 is preferably 0.5 to 2.2 parts, 1.0 to 2.2 parts, 1.5 to 2.2 parts, 1.8 to 2.2 parts, 1.9 to 2.1 parts, etc.

[0032] In the present invention, B2O3 is also a glass-forming oxide, which has boron oxide triangles [BO3] and boron oxide tetrahedrons [BO4] as structural units, and together with silicate tetrahedrons in borosilicate glass, forms a structural network. B2O3 can reduce the viscosity of glass at high temperatures and increase the viscosity of glass at low temperatures, so the glass with a higher B2O3 content has a wider forming temperature range. B2O3 also acts as a flux, accelerating the dissolution and clarification of the glass. However, when the amount of B2O3 added is too high, due to the increase in boron oxide triangles, the expansion coefficient of the glass increases, boron anomaly occurs, and the chemical stability of the glass is reduced. B2O3 is preferably 2.0 to 5.0 parts, 2.0 to 4.5 parts, 2.7 to 5.0 parts, 2.7 to 4.5 parts, 3.0 to 4.5 parts, 3.5 to 4.5 parts, 3.3 to 4.7 parts, etc.

[0033] In the present invention, the addition of Bi2O3 can improve the refractive index and dispersion ability. Bi2O3 also helps to improve the thermal stability of glass and enhance the light absorption ability, however, the introduction of Bi2O3 requires precise control. Excessive addition of Bi2O3 may lead to a significant reduction in the chemical stability of the glass. In addition, high concentrations of Bi2O3 may cause serious corrosion to the melting container during the glass melting process, which limits its application range in glass production. In addition, too much Bi2O3 may also promote glass crystallization, affecting its transparency and optical uniformity. On the contrary, insufficient Bi2O3 content makes it difficult to improve optical properties. Bi2O3 is preferably 0.1 to 3.0 parts, 0.1 to 2.5 parts, 0.1 to 2.0 parts, 0.1 to 1.5 parts, 0.1 to 1.0 parts, 0.1 to 0.9 parts, 0.3 to 0.7 parts, etc.

[0034] CeO2 is an environmentally friendly clarifier. Its clarification mechanism is that cerium oxide is a variable valence oxide. At high temperatures, cerium oxide decomposes oxygen. The more oxygen that can be separated from its chemical bonds for every 1°C increase, the greater the clarification effect. CeO2 is preferably 0.2-1.0 parts, 0.1-0.9 parts, 0.2-0.9 parts, 0.2-0.8 parts, 0.2-0.6 parts, 0.2-0.4 parts, etc.

[0035] In some embodiments, the content of Na2O is less than three times the content of K2O. Studies have shown that the glass under this composition condition has better performance.

[0036] In some embodiments, the content of B2O3 is greater than two-fifteenths of the content of Al2O3. Studies have shown that the glass under this composition condition has better performance.

[0037] In some embodiments, the content of MgO is more than twice the content of CaO. Studies have shown that the glass under this composition condition has better performance.

[0038] In some embodiments, it includes a light-transmitting effective area and / or a light-absorbing area; wherein the maximum optical transmittance of a 2 mm glass sample in the light-transmitting effective area is not less than 90.2%, preferably 90.2-92.1%, and further preferably 91.6-92.1%; the maximum optical transmittance of a 1 mm glass sample in the light-absorbing area is not higher than 1.8%, preferably 1.1-1.8%, and further preferably 1.1-1.3%.

[0039] Another embodiment of the present invention provides a method for preparing the scratch-resistant and impact-resistant photovoltaic glass cover, comprising the following steps:

[0040] Mixing the raw materials of the glass material according to the proportion of each component, and mixing them evenly to obtain a mixture;

[0041] The mixture is melted at 1480-1580°C, stirred, clarified, and molded at 1350-1400°C.

[0042] In some embodiments, the melting time is 8 to 30 hours. The glass melt is easier to clarify under this melting condition.

[0043] The glass material liquid needs to be stirred before forming to improve its uniformity, otherwise the glass material liquid is prone to stratification or agglomeration, making it difficult to melt and homogenize the glass, and even causing streaks or stone defects in severe cases. In some embodiments, the stirring speed is 15 to 30 r / min and the stirring time is 3 to 12 hours. This condition is conducive to further improving the uniformity of the glass material liquid.

[0044] In some embodiments, the molding time is 5 to 25 minutes. The invention can avoid the generation of secondary bubbles and impurities through rapid glass molding.

[0045] In some embodiments, the process further includes subjecting the formed material to a reduction blackening treatment. Specifically, the reduction blackening treatment is: heating to 500-650° C. under a reducing atmosphere for 6000-16000 min. More specifically, the pressure of the reducing atmosphere is 0.01-0.5 MPa.

[0046] In some embodiments, the formed material or the material after reduction blackening treatment or the combined material is also chemically strengthened, and the combined material is formed by melting and pressing the formed material and the material after reduction blackening treatment. Specifically, the combination method can be carried out by inserting a glass rod into the hole of a glass column. Specifically, the temperature of the chemical strengthening is 380 to 460°C, and the time is 30 to 600 minutes. Specifically, the molten salt for chemical strengthening is a potassium salt (such as potassium nitrate, potassium carbonate, etc.) and / or a sodium salt (such as sodium nitrate, sodium carbonate, etc.).

[0047] A third embodiment of the present invention provides a use of the scratch-resistant and impact-resistant optoelectronic glass cover plate in preparing a touch screen assembly for a digital product.

[0048] In some embodiments, the digital product is a mobile phone, a computer or a television.

[0049] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0050] The performance parameters in the following embodiments are measured according to the following methods:

[0051] The thermal expansion coefficient α of the glass sample was tested using the DIL 402 expansion coefficient tester produced by NETZSCH, Germany. Sample preparation: The glass sample was polished into a cylindrical glass strip of Φ6×50mm, and the two end surfaces were parallel. The heating rate was set to 5℃ / min, and the data acquisition cycle was 20ms. Refer to GB / T7962.16-2010.

[0052] The softening point temperature of the glass sample is tested using the Model PPV-1000 / 1200 plate viscometer produced by Orton. Sample preparation: The glass sample is polished into a cylindrical glass strip of Φ6×6mm, and the two end faces are parallel. The sample is placed between the top and bottom discs, which are made of heat-resistant metal alloys with a diameter of 44mm and a thickness of 6mm. The top metal disc is connected to the bottom of the probe rod. Two very thin platinum films (40mm in diameter and 0.001 inches thick) are placed between the sample and the top and bottom discs to facilitate sampling and sample placement. Refer to ASTM C-1351M.

[0053] The transmittance test was carried out using a UV-visible-infrared spectrophotometer.

[0054] After the surface of the polished glass sample is corroded by the test medium with acidity of pH2.9, pH4.6, and pH6.0, observe the time when the purple-blue interference color appears on the glass surface, or the surface becomes mottled or falls off under an incandescent lamp. The acid resistance stability of colorless optical glass is classified in descending order according to the length of time. Refer to GB / T 7962.14-2010.

[0055] Polished glass samples are kept at a constant temperature and humidity of 50°C and 85% relative humidity for 20 hours, and the moisture resistance stability of colorless optical glass is classified in descending order by comparing the turbidity values ​​with those of standard samples H (BaK7) and H (ZK9). Refer to GB / T7962.15-2010.

[0056] The CS and DOL of glass samples are tested using a glass surface stress gauge. By allowing light to propagate along the glass surface, the surface stress and stress layer depth of the strengthened glass are tested based on photoelastic technology.

[0057] The bending strength of glass samples is tested using the three-point bending method. The glass sample is processed into the required size for the test, and then the glass sample is placed between two supporting points and a fixed load is applied perpendicular to the center of the sample. Then, by applying different bending moments, the bending stress and strain of the glass are measured under different conditions. Finally, the bending strength of the glass is determined. Refer to GB / T 37781-2019.

[0058] Example 1

[0059] The components of the scratch-resistant and impact-resistant photovoltaic glass cover plate of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Tables 1, 3 and Figure 2 .

[0060] The preparation method of the scratch-resistant and impact-resistant photovoltaic glass cover is as follows: quartz sand, aluminum hydroxide, calcium carbonate, basic magnesium carbonate, potassium nitrate, sodium nitrate, lithium carbonate, zirconium oxide, boric acid, and bismuth oxide are used as raw materials, and after being fully mixed, they are melted at 1480°C for 8 hours, mechanically stirred (15r / min, 3 hours), and pressed at 1350°C (molding time is 5 minutes) to obtain a glass blank. The glass blank is placed in an annealing furnace heated to 540°C in advance for annealing to eliminate the stress in the glass to meet the requirements of later cold processing.

[0061] After annealing, the glass blank is processed into glass rods and glass columns of certain sizes by grinding and polishing the outer circle and drilling the inner holes precisely. Then, the glass rods and glass columns are placed in a blackening reduction furnace. The blackening process is set to a blackening temperature of 620°C, a reducing gas hydrogen pressure of 0.2MPa, and a blackening time of 10,000 minutes. After the blackening treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened glass rods are inserted into the holes of the glass columns that have not been blackened for melting and pressing. The melting and pressing temperature is 645°C and the pressure is 2.3×10 5 N, and then the melted glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 380°C for 500 minutes, and the molten salt ratio is 90wt% KNO3+10wt% NaNO3. After strengthening, a scratch-resistant and impact-resistant high-strength photovoltaic glass cover material is obtained.

[0062] Example 2

[0063] The components of the scratch-resistant and impact-resistant photovoltaic glass cover plate of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 1 and Figure 2 .

[0064] In the preparation method of the scratch-resistant and impact-resistant photovoltaic glass cover, the melting temperature is 1580°C, the melting time is 16 hours, mechanical stirring (30r / min, 12 hours), and 1400°C leak molding (molding time is 15 minutes) is performed to obtain a glass blank. The glass blank is placed in an annealing furnace preheated to 520°C for annealing.

[0065] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner precision holes. Then, it is placed in a blackening reduction furnace and the blackening program is set. The blackening temperature is 620℃, the reducing gas hydrogen pressure is 0.01MPa, and the blackening time is 16000min. After the blackening treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened glass rod is inserted into the hole of the glass column that has not been blackened for high-temperature melting and pressing. The melting and pressing temperature is 645℃ and the pressure is 2.3×10 5 N, and then the molten glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 460°C for 30 minutes, and the molten salt ratio is 90wt% KNO3+10wt% NaNO3. After strengthening, the scratch-resistant and impact-resistant photovoltaic glass cover material is obtained.

[0066] Example 3

[0067] The components of the scratch-resistant and impact-resistant photovoltaic glass cover plate of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Tables 1, 3 and Figure 2 .

[0068] In the method for preparing the scratch-resistant and impact-resistant photovoltaic glass cover in this embodiment, the melting temperature is 1580°C, the melting time is 30 hours, mechanical stirring (25 r / min, 12 hours), and 1400°C leak molding (molding time is 25 minutes) is performed to obtain a glass blank. The glass blank is placed in an annealing furnace preheated to 520°C for annealing.

[0069] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner hole precisely. Then, it is placed in a blackening reduction furnace and the blackening program is set. The blackening temperature is 500°C, the reducing gas hydrogen pressure is 0.5MPa, and the blackening time is 6000min. After the blackening treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened glass rod is inserted into the hole of the glass column that has not been blackened for high-temperature melting and pressing. The melting and pressing temperature is 645°C and the pressure is 2.3×10 5 N, and then the molten glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 380°C for 550 minutes, and the molten salt ratio is 90wt% KNO3+10wt% NaNO3. After strengthening, the scratch-resistant and impact-resistant photovoltaic glass cover material is obtained.

[0070] Example 4

[0071] The components of the scratch-resistant and impact-resistant photovoltaic glass cover plate of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Tables 1, 3 and Figure 2 .

[0072] In the method for preparing the scratch-resistant and impact-resistant photovoltaic glass cover in this embodiment, the melting temperature is 1560°C, the melting time is 20 hours, mechanical stirring (20 r / min, 14 hours), and pressing and molding at 1400°C (molding time is 25 minutes) to obtain a glass blank. The glass blank is placed in an annealing furnace preheated to 520°C for annealing.

[0073] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner hole precisely. Then, it is placed in a blackening reduction furnace and the blackening program is set. The blackening temperature is 650℃, the reducing gas hydrogen pressure is 0.3MPa, and the blackening time is 9000min. After the blackening treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened glass rod is inserted into the hole of the glass column that has not been blackened for high-temperature melting and pressing. The melting and pressing temperature is 645℃ and the pressure is 2.3×10 5 N, and then the melted glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 400°C for 600 minutes, and the molten salt ratio is 90wt% KNO3+10wt% NaNO3. After strengthening, the scratch-resistant and impact-resistant photovoltaic glass cover material is obtained.

[0074] Example 5

[0075] The components of the scratch-resistant and impact-resistant photovoltaic glass cover plate of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Tables 1, 3 and Figure 2 .

[0076] In the method for preparing the scratch-resistant and impact-resistant photovoltaic glass cover in this embodiment, the melting temperature is 1520°C, the melting time is 25 hours, mechanical stirring (20 r / min, 14 hours), and pressing and molding at 1380°C (molding time is 25 minutes) to obtain a glass blank. The glass blank is placed in an annealing furnace preheated to 520°C for annealing.

[0077] After annealing, the glass blank is processed into glass rods and glass columns of certain sizes by grinding and polishing the outer circle and drilling the inner holes precisely. Then, the glass rods and glass columns are placed in a blackening reduction furnace. The blackening procedure is set, and the blackening temperature is 630°C, the reducing gas hydrogen pressure is 0.2MPa, and the blackening time is 12000min. After the blackening treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened glass rods are inserted into the holes of the glass columns that have not been blackened, and high-temperature melting and pressing is performed. The melting and pressing temperature is 645°C and the pressure is 2.3×10 5N, and then the melted glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 420°C for 300 minutes, and the molten salt ratio is 90wt% KNO3+10wt% NaNO3. After strengthening, the scratch-resistant and impact-resistant photovoltaic glass cover material is obtained.

[0078] Example 6

[0079] The components of the scratch-resistant and impact-resistant photovoltaic glass cover plate of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Tables 1, 3 and Figure 2 .

[0080] In the method for preparing the scratch-resistant and impact-resistant photovoltaic glass cover in this embodiment, the melting temperature is 1560°C, the melting time is 30 hours, mechanical stirring (25 r / min, 12 hours), and 1400°C leak molding (molding time is 25 minutes) is performed to obtain a glass blank. The glass blank is placed in an annealing furnace heated to 520°C in advance for annealing.

[0081] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner precision holes. Then, it is placed in a blackening reduction furnace and the blackening program is set. The blackening temperature is 620℃, the reducing gas hydrogen pressure is 0.1MPa, and the blackening time is 13000min. After the blackening treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened glass rod is inserted into the hole of the glass column that has not been blackened for high-temperature melting and pressing. The melting and pressing temperature is 645℃ and the pressure is 2.3×10 5 N, and then the molten glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 410°C for 360 minutes, and the molten salt ratio is 90wt% KNO3+10wt% NaNO3. After strengthening, the scratch-resistant and impact-resistant photovoltaic glass cover material is obtained.

[0082] Example 7

[0083] The components of the scratch-resistant and impact-resistant photovoltaic glass cover plate of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Tables 1, 3 and Figure 2 .

[0084] In the method for preparing the scratch-resistant and impact-resistant photovoltaic glass cover in this embodiment, the melting temperature is 1560°C, the melting time is 30 hours, mechanical stirring (20 r / min, 14 hours), and pressing and molding at 1400°C (molding time is 25 minutes) to obtain a glass blank. The glass blank is placed in an annealing furnace heated to 520°C in advance for annealing.

[0085] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner precision holes. Then, it is placed in a blackening reduction furnace and the blackening program is set. The blackening temperature is 620℃, the reducing gas hydrogen pressure is 0.05MPa, and the blackening time is 15000min. After the blackening treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened glass rod is inserted into the hole of the glass column that has not been blackened for high-temperature melting and pressing. The melting and pressing temperature is 645℃ and the pressure is 2.3×10 5 N, and then the molten glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 410°C for 360 minutes, and the molten salt ratio is 90wt% KNO3+10wt% NaNO3. After strengthening, the scratch-resistant and impact-resistant photovoltaic glass cover material is obtained.

[0086] Example 8

[0087] The components of the scratch-resistant and impact-resistant photovoltaic glass cover plate of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Tables 1, 3 and Figure 2 .

[0088] In the method for preparing the scratch-resistant and impact-resistant photovoltaic glass cover in this embodiment, the melting temperature is 1570°C, the melting time is 30 hours, mechanical stirring (15 r / min, 14 hours), and 1400°C leak molding (molding time is 20 minutes) is performed to obtain a glass blank. The glass blank is placed in an annealing furnace heated to 520°C in advance for annealing.

[0089] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner hole precisely. Then, it is placed in a blackening reduction furnace and the blackening program is set. The blackening temperature is 600°C, the reducing gas hydrogen pressure is 0.3MPa, and the blackening time is 16000min. After the blackening treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened glass rod is inserted into the hole of the glass column that has not been blackened for high-temperature melting and pressing. The melting and pressing temperature is 645°C and the pressure is 2.3×10 5 N, and then the melted glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 390°C for 360 minutes, and the molten salt ratio is 90wt% KNO3+10wt% NaNO3. After strengthening, the scratch-resistant and impact-resistant photovoltaic glass cover material is obtained.

[0090] Example 9

[0091] The components of the scratch-resistant and impact-resistant photovoltaic glass cover plate of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Tables 1, 3 and Figure 2 .

[0092] In the method for preparing the scratch-resistant and impact-resistant photovoltaic glass cover in this embodiment, the melting temperature is 1560°C, the melting time is 30 hours, mechanical stirring (30 r / min, 14 hours), and pressing and molding at 1400°C (molding time is 20 minutes) to obtain a glass blank. The glass blank is placed in an annealing furnace preheated to 520°C for annealing.

[0093] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner hole precisely. Then, it is placed in a blackening reduction furnace and the blackening program is set. The blackening temperature is 600°C, the reducing gas hydrogen pressure is 0.4MPa, and the blackening time is 16000min. After the blackening treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened glass rod is inserted into the hole of the glass column that has not been blackened for high-temperature melting and pressing. The melting and pressing temperature is 645°C and the pressure is 2.3×10 5 N, and then the melted glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 400°C for 360 minutes, and the molten salt ratio is 90wt% KNO3+10wt% NaNO3. After strengthening, the scratch-resistant and impact-resistant photovoltaic glass cover material is obtained.

[0094] Comparative Examples 1 to 6

[0095] The components of the glasses of Comparative Examples 1 to 6, the weight percentage of each component, and the physical properties of the glasses obtained are shown in Tables 2, 4 and Figure 2 .

[0096] The preparation steps and parameters of the glass in Comparative Examples 1 to 6 are the same as those in Example 2.

[0097] Table 1 Components and contents of the scratch-resistant and impact-resistant photovoltaic glass cover plates of Examples 1 to 9 of the present invention

[0098]

[0099] Table 2 Components and contents of cover glass of comparative examples 1 to 6 of the present invention

[0100]

[0101]

[0102] Table 3 Performance test results of glass samples of Examples 1 to 9

[0103]

[0104]

[0105] Table 4 Performance test results of glass samples of Comparative Examples 1 to 6

[0106]

[0107]

[0108] In Tables 3-4, the samples used to test the expansion coefficient, softening point temperature, maximum optical transmittance at 350-1000nm, acid resistance stability and moisture resistance stability are glass samples before reduction blackening treatment; the samples used to test the surface compressive stress and stress layer depth are glass samples after ion strengthening; the samples with the maximum transmittance at 350-1000nm after reduction of the 1mm sample are samples after reduction blackening treatment.

[0109] In Examples 1 to 10, by reasonably adding corresponding components and controlling the ratio of each component in the raw materials, the optical transmittance, CS, DOL, bending strength and corrosion resistance of the glass are better. As can be seen from Table 3, the optical transmittance of the scratch-resistant and impact-resistant photovoltaic glass cover plates obtained in Examples 1 to 9 of the present invention is as follows: within the wavelength range of 350-1000nm, the maximum transmittance of the 2mm glass sample is ≥92.1%, and the maximum transmittance of the 1mm sample after reduction is ≤1.6%. At the same time, the acid and moisture resistance stability are both level 1, which can maintain the stability of the internal structure of the glass for a long time. After chemical strengthening, the maximum bending strength can reach 172MPa, the maximum CS is 708MPa, and the maximum DOL is 49μm. The comprehensive performance is better than the glass involved in Comparative Examples 1 to 6.

[0110] As can be seen from the above, the scratch-resistant and impact-resistant photoelectric glass cover provided by Examples 1 to 9 of the present invention has excellent optical transmittance, high bending strength, CS and DOL, excellent corrosion resistance, and good stray light elimination and processing performance. This is because in Examples 1 to 9 of the present invention, the proportion of each component raw material is adjusted in the preparation of the scratch-resistant and impact-resistant photoelectric glass cover, and a suitable stirring speed and time are set. Therefore, the scratch-resistant and impact-resistant photoelectric glass cover of the present invention has excellent optical transmittance, high bending strength, CS and DOL, excellent corrosion resistance, and good stray light elimination and processing performance, and has broad application prospects.

[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A scratch-resistant and impact-resistant photoelectric glass cover, characterized in that: In parts by weight, it is composed of the following components: SiO2 55.0~63.0 parts, Al2O3 9.0~15.0 parts, CaO 0.1~2.0 parts, MgO 4.0~8.0 parts, K2O3.0~7.0 parts, Na2O 9.0~15.0 parts, Li2O 0.5~2.0 parts, ZrO2 0.5~3.0 parts, B2O3 2.0~6.0 parts, Bi2O3 0~3.0 parts, CeO2 0.1~1.0 parts; the sum of the weight parts of each component is 100 parts.

2. The scratch-resistant and impact-resistant photovoltaic glass cover according to claim 1, characterized in that: SiO2 is 55.0-60.0 parts, or 56.5-59.0 parts, or 57.0-58.5 parts, or 57.5-58.5 parts, or 57.6-58.2 parts, or 57.8-58.2 parts; Or, Al2O3 is 9.0-14.5 parts, or 9.5-15.0 parts, or 9.5-14.5 parts, or 10.0-13.0 parts, or 10.2-13.0 parts, or 11.0-13.0 parts, or 11.5-12.5 parts; Or, CaO is 0.1-1.5 parts, or 0.1-1.0 parts, or 0.1-0.9 parts, or 0.3-0.7 parts; Or, MgO is 5.0-8.0 parts, or 5.5-8.0 parts, or 5.5-7.0 parts, or 5.5-6.5 parts; Or, K2O is 3.0-6.0 parts, or 4.0-7.0 parts, or 4.0-6.0 parts, or 4.0-5.5 parts, or 4.5-6.0, or 4.5-5.5, or 4.5-5.0, or 4.5-4.9 parts; Or, Na2O is 9.0 to 13.0 parts, or 10.0 to 13.0 parts; Or, Li2O is 0.8 to 2.0 parts, or 0.8 to 1.5 parts, or 0.8 to 1.2 parts; Or, ZrO2 is 0.5-2.2 parts, or 1.0-2.2 parts, or 1.5-2.2 parts, or 1.8-2.2 parts, or 1.9-2.1 parts; Or, B2O3 is 2.0-5.0 parts, or 2.0-4.5 parts, or 2.7-5.0 parts, or 2.7-4.5 parts, or 3.0-4.5 parts, or 3.5-4.5 parts, or 3.3-4.7 parts; Or, Bi2O3 is 0.1-3.0 parts, or 0.1-2.5 parts, or 0.1-2.0 parts, or 0.1-1.5 parts, or 0.1-1.0 parts, or 0.1-0.9 parts, or 0.3-0.7 parts; Or, CeO2 is 0.2 to 1.0 part, or 0.1 to 0.9 part, or 0.2 to 0.9 part, or 0.2 to 0.8 part, or 0.2 to 0.6 part, or 0.2 to 0.4 part.

3. The scratch-resistant and impact-resistant photovoltaic glass cover according to claim 1, wherein Na The content of K2O is less than three times that of K2O; or, the content of B2O3 is greater than two-fifteenths of the content of Al2O3; Or, the content of MgO is more than twice the content of CaO.

4. The scratch-resistant and impact-resistant photovoltaic glass cover according to claim 1, characterized in that: It includes a light-transmitting effective area and / or a light-absorbing area; wherein the maximum optical transmittance of a 2mm glass sample in the light-transmitting effective area is not less than 90.2%, preferably 90.2-92.1%, and more preferably 91.6-92.1%; the maximum optical transmittance of a 1mm glass sample in the light-absorbing area is not higher than 1.8%, preferably 1.1-1.8%, and more preferably 1.1-1.3%.

5. A method for preparing the scratch-resistant and impact-resistant photovoltaic glass cover plate according to claim 1, characterized in that: The steps include: Mixing the raw materials of the glass material according to the proportion of each component, and mixing them evenly to obtain a mixture; The mixture is melted at 1480-1580°C, stirred, clarified, and molded at 1350-1400°C.

6. The method for preparing the scratch-resistant and impact-resistant photovoltaic glass cover plate according to claim 5, characterized in that: The melting time is 8 to 30 hours; Or, the stirring speed is 15-30 r / min, and the stirring time is 3-12 h; Or, the molding time is 5 to 25 minutes.

7. The method for preparing the scratch-resistant and impact-resistant photovoltaic glass cover plate according to claim 5, characterized in that: It also includes a process of reducing and blackening the formed material; preferably, the reducing and blackening treatment is: heating to 500-650°C under a reducing atmosphere for 6000-16000 minutes; preferably, the pressure of the reducing atmosphere is 0.01-0.5 MPa.

8. The method for preparing the scratch-resistant and impact-resistant photovoltaic glass cover plate according to claim 5 or 7, characterized in that: It also includes chemically strengthening the formed material or the material after reduction blackening treatment or the combined material, wherein the combined material is formed by melting and pressing the formed material and the material after reduction blackening treatment; preferably, the combination method can be carried out by inserting a glass rod into the hole of a glass column; preferably, the temperature of the chemical strengthening is 380-460°C and the time is 30-600min.

9. An application of the above-mentioned scratch-resistant and impact-resistant optoelectronic glass cover in the preparation of a touch screen component for a digital product.

10. The use according to claim 9, characterized in that: The digital product is a mobile phone, a computer or a television.